Design and simulation of vehicle entry detection circuit based on ground induction coil - Zhou Ya; Dai Wei; Zhang Xin; Xu Li (Dianzi Jishu Yingyong)
In the field of traffic Internet of Things, there is a business demand for road traffic flow information monitoring. The ground sensing coil is arranged on the road to sense the information of vehicles entering and provide initial data for the traffic Internet of Things. According to the working scene of ground induction coil, the working principle of ground induction coil is described. On this basis, a circuit of vehicle entry detection signal based on ground induction coil is designed. The signal acquisition circuit is mainly composed of tuning oscillation circuit, waveform shaping circuit and microprocessor. The design points of each module are introduced. PSpice software simulation shows that the circuit can effectively collect the state value change of ground sensing coil, so as to detect vehicle entry. It has high practical value and application prospect in the field of traffic Internet of Things.